Effects of the unilateral removal and dissection of the masseter muscle on the facial growth of young rats - Lucimar Rodrigues; Andréia Aparecida Traina; Luiz Felipe Nakamai; João Gualberto de Cerqueira Luz (Sociedade Brasileira de Pesquisa Odontológica, 2009)
This study analyzed the effects of the unilateral removal and dissection of the masseter muscle on the facial growth of young rats. A total of 30 one-month-old Wistar rats were used. Unilateral complete removal of the masseter muscle was performed in the removal group, and detachment followed by repositioning of the masseter muscle was performed in the dissection group, while only surgical access was performed in the sham-operated group. The animals were sacrificed at three months of age. Axial radiographic projections of the skulls and lateral projections of the hemimandibles were taken. Cephalometric evaluations were made and the values obtained were submitted to statistical analyses. In the removal group, there were contour alterations of the angular process, and a significant homolateral difference in the length of the maxilla and a significant bilateral difference in the height of the mandibular body and the length of the mandible were observed. Comparison among groups revealed significance only in the removal group. It was concluded that the experimental removal of the masseter muscle during the growing period in rats induced atrophic changes in the angular process, as well as asymmetry of the maxilla and shortening of the whole mandible.